Experimental study on deterioration characteristics of foamed concrete under dry-wet cycles in acidic environment - Wu, Yongmei; Chai, Shaoqiang; Chen, Yong; Zou, Songzhe; Chai, Lianzeng (Frontiers in Materials, 2024)
Foamed concrete, which has excellent performance, has been gradually used to enhance the thermal insulation performance of buildings in recent years. However, there are few studies on the durability of foamed concrete under environmental action. In order to understand the law of damage and deterioration of foamed concrete under dry-wet cycles in acidic environment, the standard sample of foamed concrete was first pre-treated with different times of dry-wet cycles under neutral and two acidic environments, then quality inspection, uniaxial compression test and scanning electron microscope were carried out on the treated foamed concrete by electronic scale, universal testing machine and electron microscope. Accordingly, the deterioration effect and deterioration mechanism of foamed concrete under dry-wet cycles in acidic environment is analyzed. The results show that the quality and uniaxial compressive strength of foamed concrete decrease gradually with the increase of the number of dry-wet cycles in both neutral and two acidic environments; the stronger the acidity of dry-wet cycles, the more the quality of foamed concrete decreases and the more obvious the deterioration effect of uniaxial compressive strength of foamed concrete; the acidic dry-wet cycles will corrode the foamed concrete, resulting in the expansion and consolidation of pores and the appearance of cracks, and the more the number of dry-wet cycles, the more obvious the corrosion effect of the foamed concrete. The research results can provide scientific basis for the analysis of the safety and stability of foamed concrete members under the dry-wet cycle in acidic environment.